Behavior influencing factors of teenagers studying at boarding elementary school - Kolendoviča, Indra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Social environment where people live, propose definite requirements. School proposes requirements that deal with a successful acquisition of study subjects, maintenance of communication with classmates and teachers, regulation of own behaviour in order it could be acceptable in the context of social relation (Raščevska et all, 2010). In interaction with other people (social models) there appear cognitive schemes and regulation systems that determine behaviour (Costa, 2008;Jessor, 1992; Muris, 2006). Behaviour problems are more common for a teenage period. They become especially acute for teenagers who come from a socially unfavourable environment and that is the reason for excluding them from an active involvement into class and school activities, there often happens segregation. The aim of the paper is to set risk factors for teenagers’ behaviour at elementary boarding school.